Influence of the Hollowness and Size Distribution on the Magnetic Properties of Fe3O4 Nanospheres - Shi, Yang (Langmuir : the ACS journal of surfaces and colloids, 2021)
In this study, Fe3O4 nanospheres with different levels of hollowness were successfully prepared by the solvent thermal method. The synthesized Fe3O4 nanospheres were characterized by transmission electron microscopy, X-ray diffraction, and vibrating sample magnetometry, and Image-Pro software was used to analyze the hollowness of the Fe3O4 nanospheres for the first time. It was found that excess reactants could lead to the disappearance of the hollow structure of the Fe3O4 nanospheres, and the reason for this phenomenon was discussed as due to entropy increase theory. Furthermore, the influence of the hollowness and size distribution on the magnetic properties of the Fe3O4 nanospheres was evaluated. The magnetic properties of a Fe3O4 nanosphere with a hollowness of 10.48% showed a relatively high saturation magnetization of 103 emu/g and a rather low coercivity (54 Oe). The as-prepared Fe3O4 nanospheres are expected to be useful in a wide range of fields such as drug-delivery and energy applications